FUNDAMENTAL BEHAVIOR FOR BIOSORPTION OF DIVALENCE CATIONS BY PLEUROTUS MUSHROOM SPENT-SUBSTRATE - Tay, Chia-Chay; Redzwan, Ghufran; Hooi, Liew Hong; Kong, Yong Soon; Surif, Salmijah; Abdul-Talib, Suhaimi (Malaysian Journal of Science, 2011)
Biosorption behavior of Pleurotus mushroom spent-substrate was studied using two divalence cations: Ni(II) and Cu(II). Biosorption of both cations showed similar behavior on the effect of pH, initial concentration, temperature and contact time. Optimum biosorption was found to be between pH of 5-6, while lower initial concentration and temperature (as low as 10 mg.L-1 and 5 oC), increased the biosorption efficiency. Rapid biosorption was observed to occur within 4-5 minutes of contact time. Therefore, metal removal using PMSS as the biosorbent needs to address the four fundamental parameters. Kelakuan biopenjerapan bagi substrat terpakai cendawan Pleurotus dikaji dengan menggunakan dua kation dua valensi iaitu Ni(II) dan Cu(II). Faktor pH, kepekatan awal larutan, suhu dan masa interaksi memberikan kesan yang sama terhadap kedua kation yang dikaji. pH 5-6 merupakan paras pengoptimuman biopenjerapan. Sementara itu, kepekatan awal larutan dan suhu yang rendah (serendah 10 mg.L-1 dan 5 oC) telah meningkatkan kecekapan biopenjerapan. Kadar biopenjerapan maksima berlaku dalam tempoh masa bersentuhan selama 4-5 minit. Oleh itu, faktor pemboleh-ubah operasi penyingkiran logam dengan menggunakan PMSS sebagai bahan biopenjerap perlu mengambilkira empat kelakuan asas. (Keywords: biosorption behavior, Pleurotus sp., metal, mushroom spent-substrate)